2012
DOI: 10.1007/s00431-012-1907-1
|View full text |Cite
|
Sign up to set email alerts
|

Acne vulgaris is associated with intensive pubertal development and altitude of residence—a cross-sectional population-based study on 6,200 boys

Abstract: Our results showed that the development of acne vulgaris in male adolescents was associated with an intensive growth and pubertal maturation, while obesity per se did not play an important role. Of particular interest was the association between the prevalence of acne and the altitude of residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
10
1
3
Order By: Relevance
“…According to a systematic review and meta-analysis, the prevalence rates of acne in the southern China was higher than that of the northern China, because the southern part is more humid and warmer than the north ( 84 ). A study also showed that the higher the altitude, the lower the prevalence of acne, which may be related to higher altitudes and lower temperature and humidity ( 85 ). The above studies indicated that hot weather might aggravate acne, but further quantitative studies are needed on the relationship between humidity and acne.…”
Section: Resultsmentioning
confidence: 99%
“…According to a systematic review and meta-analysis, the prevalence rates of acne in the southern China was higher than that of the northern China, because the southern part is more humid and warmer than the north ( 84 ). A study also showed that the higher the altitude, the lower the prevalence of acne, which may be related to higher altitudes and lower temperature and humidity ( 85 ). The above studies indicated that hot weather might aggravate acne, but further quantitative studies are needed on the relationship between humidity and acne.…”
Section: Resultsmentioning
confidence: 99%
“…In another publication, the same authors state that the minimal clinical important difference of the DLQI is reported to be between 2.2 and 6.9 depending on the skin disease BDI: self-administered questionnaire with 21 questions. Patients categorised as minimal (score 0-9), mild (score 10-18), moderate (score [19][20][21][22][23][24][25][26][27][28][29] or severe (score 30-36) depression…”
Section: Methodsmentioning
confidence: 99%
“…31 Contudo, quando se estudaram outras variáveis, para além do IMC, como o crescimento somático, maturação pubertal e fatores ambientais com a acne, numa população do género masculino até os 19 anos, a obesidade, por si só, não parece apresentar um papel importante no aparecimento da acne. 37 Robeva et al, mostraram também que apenas o IMC de adolescentes com 15 anos de idade com acne estava aumentado em comparação com os indivíduos da mesma idade saudáveis (21,80 ± 2,93 vs 20,89 ± 3,00, p = 0,003), não existindo diferença de peso e IMC entre adolescentes mais velhos com e sem acne. 37 O excesso de peso/obesidade é também um fator de risco para o desenvolvimento de síndrome metabólica, caraterizada pela obesidade central, formada pelo tecido adiposo visceral, hipertrigliceridemia, baixos níveis de HDL, hiperglicemia e hipertensão.…”
Section: Benefícios De Dietas De Baixo íNdice Glicémicounclassified
“…37 Robeva et al, mostraram também que apenas o IMC de adolescentes com 15 anos de idade com acne estava aumentado em comparação com os indivíduos da mesma idade saudáveis (21,80 ± 2,93 vs 20,89 ± 3,00, p = 0,003), não existindo diferença de peso e IMC entre adolescentes mais velhos com e sem acne. 37 O excesso de peso/obesidade é também um fator de risco para o desenvolvimento de síndrome metabólica, caraterizada pela obesidade central, formada pelo tecido adiposo visceral, hipertrigliceridemia, baixos níveis de HDL, hiperglicemia e hipertensão. 38 Existem várias evidências que o desenvolvimento de síndrome metabólica se encontra associada ao aparecimento da acne.…”
Section: Benefícios De Dietas De Baixo íNdice Glicémicounclassified